Doping of MXenes enhances the electrochemical response of peptide-imprinted conductive polymers for the recognition of C-Reactive protein - Lee, Mei-Hwa; Liu, Kai-Hsi; Thomas, James L.; Chen, Chen-Yuan; Chen, Chuen-Yau; Yang, Chien-Hsin; Lin, Hung-Yin (Biosensors & bioelectronics, 2022)
The level of C-reactive protein (CRP) in serum is frequently used to evaluate risk of coronary heart disease, and its concentration is related to cardiovascular disease, fibrosis and inflammation, cancer, and viral infections. In this work, three novel peptides, never previously used as imprinted templates, were selected, synthesized, and employed for epitope imprinting. Various imprinting concentrations of the template and various ratios of aniline (AN) to m-aminobenzenesulfonic acid (MSAN) were used in electropolymerization to form molecularly imprinted polymers (MIPs). The imprinting template and functional monomer concentrations were optimized to maximize the electrochemical response to target peptides. The surface morphologies of peptide- and non-imprinting poly(AN-co-MSAN) were observed using a scanning electron microscope (SEM) and an atomic force microscope (AFM). Moreover, the effect of doping of MIPs with a very small percentage of an MXene (e.g. Ti2C at 0.1 wt% in the preparation solution) on the electrochemical response was also studied. Ti2C doping dramatically increased sensing range from 0.1 to 100 fg/mL to 10000 fg/mL, and electrochemical responses were amplified by a factor of approximately 1.3 within the sensing range. Finally, commercially available serum was diluted and then measured using the MXene-doped PIP-coated electrodes to estimate the accuracy compared with ELISA results. •Three novel peptides of CRP were synthesized as templates for molecular imprinting.•The epitope imprinting compositions were optimized to maximize the electrochemical response.•Doping of Ti2C dramatically increased sensing range from 0.1 to 100 fg/mL to 10000 fg/mL.